1999
DOI: 10.1021/ma990339+
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Characterization of Short Chain Branches of Nickel Catalyzed Polyethylene

Abstract: All peaks in the 13C NMR spectrum of a sample of nickel-catalyzed polyethylene can be assigned to linear short chain branches having specific spatial arrangements along the polymer backbone. The chain walking mechanism of branch formation controls the specific spacing and conformational arrangements between these linear short chains. Certain unusual short chain branching sequences, involving two branches separated either by two or four methylene backbone carbons, were observed. Invariably one of the two branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 10 publications
4
55
0
Order By: Relevance
“…[21] The position information of methine peaks could also be used in this analysis. [22][23][24][25] Rinaldi et al [26] provided an indepth study and observed chemical shift differences of 0.003-0.007 ppm between the peak positions of CH(B 6 ) (38.283 ppm), CH(B 8 ) (38.286 ppm), and CH(B 10 ) (38.293 ppm) in 188.6 MHz 13 C NMR spectra. Such differences could be enhanced by an order of magnitude through adjusting temperature and sample concentration.…”
Section: Nmrmentioning
confidence: 99%
“…[21] The position information of methine peaks could also be used in this analysis. [22][23][24][25] Rinaldi et al [26] provided an indepth study and observed chemical shift differences of 0.003-0.007 ppm between the peak positions of CH(B 6 ) (38.283 ppm), CH(B 8 ) (38.286 ppm), and CH(B 10 ) (38.293 ppm) in 188.6 MHz 13 C NMR spectra. Such differences could be enhanced by an order of magnitude through adjusting temperature and sample concentration.…”
Section: Nmrmentioning
confidence: 99%
“…The 13 C NMR spectrum of the 4-methyl-1-hexene/ethylene copolymer is presented in Figure 2. The polymer was found to contain approximately 0.8 mole percent 4-methyl-1-hexene by 13 C NMR analysis. The most interesting peaks in this polymer sample are those assigned to the backbone methylene carbons S ␣␦ϩ , S ␤␦ϩ , and S ␥␦ϩ .…”
Section: Resultsmentioning
confidence: 99%
“…1,2,[11][12][13] However, the spectra of polymers are often very complex and the exact structural relationship between branches is unknown, making assignment of resonances difficult. A great help in the assignment of chemical shifts to structural forms comes from the ability to theoretically predict chemical shift values 14 -17 or through the synthesis of model compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38] High-resolution 13 C NMR has ben used for this application. With this technique, shifts in the radio-frequency vibrations of up to five carbon atoms from a branch point have been estimated 39 and can be used to calculate the number density of branches.…”
Section: Determination Of the Branch Content In Polymers And Ceramicsmentioning
confidence: 99%